The quantum-confined Stark effect in layered hybrid perovskites mediated by orientational polarizability of confined dipoles. Issue 1 (December 2018) - Walters, G.; Wei, M.; Voznyy, O.; Quintero-Bermudez, R.; Kiani, A.; Smilgies, D.-M.; Munir, R.; Amassian, A.; Hoogland, S.; Sargent, E.
Abstract The quantum-confined Stark effect (QCSE) is an established optical modulation mechanism, yet top-performing modulators harnessing it rely on costly fabrication processes. Here, we present large modulation amplitudes for solution-processed layered hybrid perovskites and a modulation mechanism related to the orientational polarizability of dipolar cations confined within these self-assembled quantum wells. We report an anomalous (blue-shifting) QCSE for layers that contain methylammonium cations, in contrast with cesium-containing layers that show normal (red-shifting) behavior. We attribute the blue-shifts to an extraordinary diminution in the exciton binding energy that arises from an augmented separation of the electron and hole wavefunctions caused by the orientational response of the dipolar cations. The absorption coefficient changes, realized by either the red- or blue-shifts, are the strongest among solution-processed materials at room temperature and are comparable to those exhibited in the highest-performing epitaxial compound semiconductor heterostructures. The quantum-confined Stark effect is conventionally observed in inorganic semiconductor multilayer quantum well structures that are expensive to make. Here Walters et al. report large Stark effects in easily made layered hybrid perovskites and exploit the orientational polarizability of dipolar cations.